FACTORS AFFECTING CONTRAPRODUCTIVE BEHAVIOR TREND OF PDAM EMPLOYEES IN PADANG, WEST SUMATERA - Tun Huseno (Jurnal Ilmu Pemerintahan Widya Praja, 2023)
The phenomenon of counterproductive behavior is not uncommon in the workplace, including private companies, BUMN/BUMD and government offices. Counterproductive behavior can have a negative impact on the long-term existence of the organization as it hinders the organization from achieving its desired goals. This study aims to identify the factors influencing the tendency of counterproductive behavior, namely narcissism, person job fit, person organizational environment fit and collective culture towards counterproductive behavior in PDAM (Municipal Water Utility Company) employees in Padang, West Sumatera. The sample used in this study was 155 respondents. The analytical method used is multiple linear regression analysis using the statistical t test. Based on the results of the study, it was found that narcissism indeed has a significant effect on counterproductive behavior tendencies. On the contrary, person job fit, individual suitability for the work environment and collective culture have no significant effect on counterproductive behavior. Key words: Narcissism; person - job fit, person work environment fit, Collective Culture and Counter Productive Behavior